PENGARUH ENKAPSULASI BENIH CABAI RAWIT (Capsicum frutescens L.) DENGAN BERBAGAI BAHAN PEMBAWA PADA BAHAN AKTIF Trichoderma spp. UNTUK PENGENDALIAN PENYAKIT LAYU FUSARIUM - Hidayat, Taufik; Nirwanto, Herry; Wuryandari, Yenny (Universitas Lampung, 2025)
Fusarium wilt is an important disease of cayenne pepper plants caused by the fungus Fusarium. Trichoderma is a type of biological agent that can be used to control plant diseases, one of which is fusarium wilt. This research was conducted to determine the effect of seed encapsulation with different carrier materials and the active ingredient Trichoderma in controlling fusarium wilt disease. This research was carried out in September 2023-January 2024, at the Plant Health Laboratory and Green House of UPN